2019
DOI: 10.1093/biostatistics/kxz014
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian adaptive basket trial design using model averaging

Abstract: Summary In this article, we develop a Bayesian adaptive design methodology for oncology basket trials with binary endpoints using a Bayesian model averaging framework. Most existing methods seek to borrow information based on the degree of homogeneity of estimated response rates across all baskets. In reality, an investigational product may only demonstrate activity for a subset of baskets, and the degree of activity may vary across the subset. A key benefit of our Bayesian model averaging appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 19 publications
3
58
0
Order By: Relevance
“…Ventz et al 227 proposed a general class of Bayesian basket trial designs using Bayesian hierarchical models and response-adaptive randomization, which facilitate both identification of a biomarker subpopulation, and identification of a subset of, for example, cancers within a biomarker-defined subpopulation that benefits from a treatment. The most recent design was proposed by Psioda et al, 228 who proposed an adaptive Bayesian basket trial design using Bayesian model averaging, which allows for some baskets to share a similar efficacy and for some to have a unique efficacy. Using simulation studies and different scenarios, the authors found that compared with basket trial designs proposed earlier, their framework achieves steady performances with respect to certain operating characteristics, such as expected sample size and different error rates.…”
Section: Basket Designs and Methodsmentioning
confidence: 99%
“…Ventz et al 227 proposed a general class of Bayesian basket trial designs using Bayesian hierarchical models and response-adaptive randomization, which facilitate both identification of a biomarker subpopulation, and identification of a subset of, for example, cancers within a biomarker-defined subpopulation that benefits from a treatment. The most recent design was proposed by Psioda et al, 228 who proposed an adaptive Bayesian basket trial design using Bayesian model averaging, which allows for some baskets to share a similar efficacy and for some to have a unique efficacy. Using simulation studies and different scenarios, the authors found that compared with basket trial designs proposed earlier, their framework achieves steady performances with respect to certain operating characteristics, such as expected sample size and different error rates.…”
Section: Basket Designs and Methodsmentioning
confidence: 99%
“… Pfalse[pi>p0false|scriptDfalse]>τE.Used by: Psioda et al. (2019). As for the futility assessment one can change the reference value which then results in Ppi>p0+p12|D>τE.Used by: Berry et al.…”
Section: Analysis Of Basket Trialsmentioning
confidence: 99%
“…At the interim analysis with the total sample size of N total /2, if Pr [ p k ≥ 0.05| r , n ] < 0.2 (= c interim ) ( k = 1, ⋯, K ), enrollment for subpopulation ( k ) was terminated. Consistent with the simulation studies reported by Psioda et al and Simon et al 25,27 , we used the value of 0.2 for c inerim . At the final analysis, we ultimately determined treatment effectiveness in subpopulation ( k ) when Pr [ p k ≥ 0.05| r , n ] > 0.9 (= c final ) ( k = 1, ⋯, K ) was satisfied.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…Apart from these methods, recent work done by Psioda et al 25 proposed to use the Bayesian model averaging 26 to estimate the response rate of each subpopulation. The Bayesian model averaging strategy is a computer‐intensive design that averages the response rate overall possible models for evaluating a similarity in response rates among subpopulations.…”
Section: Introductionmentioning
confidence: 99%